Hasil Belajar Matematika Siswa Ditinjau Dari Kecemasan Matematika dan Fasilitas Belajar di Rumah - Ibrahim Ibrahim; Rokyul Amin (Jurnal Pendidikan Matematika:Judika Education, 2021)
This study aims to determine the effect of mathematics anxiety, learning facilities at home, and the effect of mathematics anxiety and learning facilities at home simultaneously on students' mathematics learning outcomes. The approach in this research uses a quantitative approach, the type of correlational research. This research was conducted at SMP Negeri 1 Bayat in grades VIII A and VIII B in the 2020/2021 school year. The sample used was 30 students, the sampling technique was simple random sampling. The instrument used to use data from the mathematics anxiety scale test and the home learning facility scale test. The data analysis technique in this study used multiple regression analysis. Data analysis was carried out with the help of the SPSS 25 application. The results of this study indicate that: 1) there is a negative effect of mathematics anxiety on students' mathematics learning outcomes; 2) there is a positive effect of home learning facilities on students' mathematics learning outcomes; 3) there is an effect of mathematics anxiety and learning facilities at home together on students' mathematics learning outcomes. Keywords: Mathematics Anxiety, Learning Facilities at Home, Mathematics Learning Outcomes